(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the effectiveness of oral hygiene performed by caregivers of children and adolescents with cerebral palsy (CP) during the moments before and after three months of oral health instructions. Methods: In a longitudinal study, 102 participants were joined in two groups: G1 (n=51) composed of children and adolescents (C/A) with CP and G2 (n=51), composed of their caregivers. Sociodemographic and oral hygiene habits were collected and evaluated using the Visible Plaque Index (VPI) and Gingival Bleeding Index (GBI), before and after oral hygiene orientation. The Qui-Squared, ANOVA 1, and tStudent tests were applied. P < 0,05. Results: The C/A group with pattern clinical CP tetraparesis, diparesis and hemiparesis were homogeneous in terms of gender (P = 0,07), however differed in age (P < 0,05), the youngest being diparetic. No difference was observed when comparing VPI and GBI before and after instructions in oral health for the three clinical types (P> 0,05). However, a reduction in the VPI and GBI indexes (P < 0,05) before and after, in each of the three clinical patterns. Most of the caregivers were female, married, with a high school degree, and they performed oral hygiene three times per day. The caregivers presented significant drops in VPI and GBI after receiving oral hygiene instructions. (P < 0,05). Conclusion: Oral hygiene instruction is fundamental for the caregivers of children and adolescents with cerebral palsy since it is an effective form of controlling health problems.